Let's bee thankful - Burach, Ross (Burach, Ross. Bumble and Bee, 2020)
In autumn, Bumble and Bee are excited to paint pumpkins and help Froggy make a special apple pie; but when the weather turns frosty, Froggy decides to find a quiet place to settle in for the winter unless Bumble and Bee can tempt Froggy into one more adventure.